2017
DOI: 10.1016/j.jcv.2017.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Real-world performance of the new US HIV testing algorithm in medical settings

Abstract: Background Our medical center laboratory recently adapted its 24/7, two-hourly testing program to use an ARCHITECT-Multispot-viral load (AR-MS-VL) algorithm in place of a previous rapid test-immunofluorescence (RT-IF) algorithm. Objectives We evaluated screening test performance, acute case detection, turnaround time and ability to resolve HIV status under the new algorithm. Study Design We considered consecutive HIV tests from January-November 2015. AR-MS-VL results at Zuckerberg San Francisco General Hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Although no single S/CO ratio can reliably distinguish a true-positive from a false-positive HIV antigen/antibody test, the S/CO ratio can serve as a valuable diagnostic tool, informing posttest probability of disease and influencing medical decision-making. 12,14,19–22 In fact, based on the S/CO ratio alone, 82% of the 1035 ED patients in our study with a reactive HIV antigen/antibody test could be classified with a high degree of diagnostic certainty: with 9% classified as being very unlikely to have HIV (S/CO < 1.58) and 73% classified as being very likely to have HIV (S/CO ≥ 20.7). This left only 18% of ED patients with a reactive HIV antigen/antibody test in a diagnostic grey area (those with S/CO ratios between 1.58 and 20.7) whose posttest probability of being HIV-positive was approximately 30%.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Although no single S/CO ratio can reliably distinguish a true-positive from a false-positive HIV antigen/antibody test, the S/CO ratio can serve as a valuable diagnostic tool, informing posttest probability of disease and influencing medical decision-making. 12,14,19–22 In fact, based on the S/CO ratio alone, 82% of the 1035 ED patients in our study with a reactive HIV antigen/antibody test could be classified with a high degree of diagnostic certainty: with 9% classified as being very unlikely to have HIV (S/CO < 1.58) and 73% classified as being very likely to have HIV (S/CO ≥ 20.7). This left only 18% of ED patients with a reactive HIV antigen/antibody test in a diagnostic grey area (those with S/CO ratios between 1.58 and 20.7) whose posttest probability of being HIV-positive was approximately 30%.…”
Section: Discussionmentioning
confidence: 75%
“…We demonstrated that ED patients with acute HIV infection, compared with those with chronic infection, tend to have lower S/CO ratios and that S/CO ratios in these lower ranges likely represent more recent HIV infection, a finding previously described in non-ED testing sites. 12,14,15,19,22 The S/CO ratio, however, cannot accurately distinguish between acute and chronic infections. Practically, this means EPs must consider acute HIV infection in every patient with a reactive HIV antigen/antibody test and pay particular attention to those with lower S/CO ratios by performing a focused clinical evaluation looking for signs and symptoms of acute HIV infection and recent HIV exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies include a PPV for the screening test as well as a suggested S/Co ratio for optimal screening test performance. Study N = PPV Median S/Co ratio of True Positives (Range) Median S/Co ratio of False Positives (Range) Optimal S/Co ratio (100 % sensitivity maintained unless otherwise stated) Significance of difference in S/Co ratios Marson et al [12] 5518 44 % 15 (Low risk setting) Jensen et al [9] 138,911 69 % 328.3 (1.1–1493.6) 1.9 (1.0–151.17) P < 0.0001 Baltaro et al [4] 61,666 5 (100 when WBC > 6.5) Alonso et al [3] 69,471 91 % 660.74 (2.91–1392.12) 2.31 (1.02–130.36) 2.5 (ROC) P < 0.0001 Hodgson et al [8] 11,987 46 % 826 (199–1094) 2 (1–39) Ramos et al [15] 21,317 87 % 794 ≈ 2 Chavez et al [5] 10,995 411.9 2.9 Zhang et al [26] 692,155 79 % overall (46 % for female samples) 352.17 1.77 Males: 8.96 (ROC) Females: 26.97 (ROC) P < 0.05 White et al [21] 1035 reactive screens 78 % 539.2 (1.58–1867.6) 1.93 (1.0–363) 20.7 by ROC (sensitivity 93.2 %) P < 0.001 Cui et al ...…”
Section: Discussionmentioning
confidence: 99%
“…This builds upon the existing HIV testing algorithm to stratify patients as "presumptive HIV positive" versus "likely false-positive fourth-generation screening test" based upon the S/CO ratio generated by the fourth-generation test. Multiple studies, including ours, have demonstrated high sensitivity and specificity when a S/CO ratio of >10-15 is useful to predict true HIV positivity [5][6][7][8][9]. Our study is unique in that we examined this cutoff in the specific patient population in which follow-up testing is challenging, those with positive fourth generation tests and negative supplemental tests.…”
Section: Plos Onementioning
confidence: 99%